Nanoscale polarization relaxation of epitaxial BiFeO3 thin film - Chen, Weigang (2011)
The polarization relaxation phenomena in a 40-nm-thick epitaxial BiFeO3 thin film grown on a (001) SrTiO3 substrate with SrRuO3 bottom electrode, was studied in nanoscale using dual-frequency resonance-tracking piezoresponse force microscopy. The as-grown film shows highly irregular mosaic domain pattern. The nucleation of reversed domains followed by domain wall propagation and domain coalesce was observed during relaxations. The polarization relaxation follows a stretched exponential model f = 1 - e^(-k(t-t0)^n) with parameters t0 = 2894 s, n =0.50 and k =6.04e-4. Local polar defects act as nucleation centers and the time-dependent depolarization field is the driving force for polarization relaxation.